Non-HDL Cholesterol as a Predictor of Cardiovascular Disease in Type 2 Diabetes (Medical Forum Monthly, 2022)
Objective: To analyze the role of non-HDL-Cholesterol as an indicator for the development of CVD in Pakistan’s population with type 2 diabetes mellitus (T2DM).Study Design: Cross-sectional analytical studyPlace and Duration of Study: This study was conducted at the department of Cardiology diabetic Centre at Ch. Pervaiz Elahi Institute of Cardiology Multan from June 2020 to June 2021 for a period of one year.Materials and Methods: The study included 90 subjects, 50 cardio paths with T2DM and 40 control. Standard enzymatic procedures were used to establish biochemical balance. A questionnaire was used as a means of collecting information about pathologies.Results: The logistic model showed two levels of non-HDL-C: 130 mg/dl < non-HDL-C ≤ 160 mg/ dl (OR = .12, P=.002, 95% CI = .02-0.48) and 160 mg/dl < non-HDL-C ≤ 190 mg/dl (OR = 5.03, P =.036, 95% CI = 1.2-22.88) and smoking (OR= 19.28, P = .00295% CI = 3.38-109.64 ), inbreeding (OR = 3.66, P = .032,95% CI = 1.13-11.86) and 2 age groups 60-70 years (OR = 2.37, P<0.05,95% CI = 1.33-4.3) and those of 70 years or above (OR = 2.27, P<0.0595% CI = 1.18-4.28).Conclusion: Non-HDL-C is a potential risk factor for the development of CVD in patients with T2DM in Pakistan